2016
DOI: 10.1098/rspb.2016.0216
|View full text |Cite
|
Sign up to set email alerts
|

Naked mole rats exhibit metabolic but not ventilatory plasticity following chronic sustained hypoxia

Abstract: ResearchCite this article: Chung D, Dzal YA, Seow A, Milsom WK, Pamenter ME. 2016 Naked mole rats exhibit metabolic but not ventilatory plasticity following chronic sustained hypoxia. Naked mole rats are among the most hypoxia-tolerant mammals identified and live in chronic hypoxia throughout their lives. The physiological mechanisms underlying this tolerance, however, are poorly understood. Most vertebrates hyperventilate in acute hypoxia and exhibit an enhanced hyperventilation following acclimatization to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…However, ventilation accounts for only part of the hypoxic response as many semi‐fossorial and fossorial species employ a strategy that also includes decreases in metabolism . NMRs combat low environmental O 2 with a large reduction in aerobic metabolism, thus matching O 2 demand to a depleted O 2 supply . The mole‐rat species reported in this study, with the exception of G.c.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, ventilation accounts for only part of the hypoxic response as many semi‐fossorial and fossorial species employ a strategy that also includes decreases in metabolism . NMRs combat low environmental O 2 with a large reduction in aerobic metabolism, thus matching O 2 demand to a depleted O 2 supply . The mole‐rat species reported in this study, with the exception of G.c.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work has shown that the NMR is among the most hypoxia‐tolerant mammals, responding to extreme hypoxia with no change in ventilation and large reductions in metabolism (Figure ). This is hypothesized to be the result of an evolutionary pressure exerted by low oxygen availability resulting from their fully fossorial and eusocial lifestyle, which could possibly be facilitated by a retention of neonatal traits .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure ). Physiologically, these animals show a high tolerance to hypoxic and hypercapnic conditions (Chung, Dzal, Seow, Milsom, & Pamenter, ; Larson & Park, ; Nevo, ; Park et al, ). Their sensory organs have also adapted to the dark and featureless underground environment (Burda, Bruns, & Müller, ).…”
Section: Introductionmentioning
confidence: 99%